Automated pavement marking integrity assessment using a UAV platform–a test case of public parking - Rahnamayiezekavat, Payam; Wang, Di; Chai, Jian; Moon, Sungkon; Rashidi, Maria; Wang, Xiangyu (Journal of Asian Architecture and Building Engineering, 2024)
Intact pavement markings organize the utilization of the pavement surface area, increase the road capacity, and improve traffic safety. However, deterioration occurring over the service life will lead to traffic safety hazards. A detailed inspection is regarded as the central tenet of pavement marking management. Conventional manual assessment approaches are time-consuming, qualitative, and argued to be subjective. Thus, cost reduction, quantitative analysis, and automatization have been the focus of research. Unmanned Aerial Vehicle (UAV) platform has been studied wildly in civil tasks due to its low cost and high maneuverability. A UAV-based platform was developed in this research to address the inefficiency, access limitations, and image processing of existing road marking inspection systems. In this research, the resolution of the image is 5472 × 3080 pixels and is captured with a fixed focal length of 8.8 mm. Given intensity differences between pixels of paintings and asphalt backgrounds, the pixels belonging to painting regions are classified using the K-mean clustering algorithm. After detecting all parking lines from images, the Otsu method was employed to determine the threshold of 0.9 as the quantitative indicator of painting quality. The UAV-based platform exhibits expected performance in assessing the pavement markings in a parking area. Future research will explore the deployment in city-scale applications.
Keywords: Aerial vehicle; Images processing; Integrity assessment; Pavement marking management; Pavement markings; Quality assessment; Test case; Traffic safety; Unmanned aerial vehicle; Vehicle platforms; image processing; pavement marking management; quality assessment; Unmanned aerial vehicle (UAV)